2016
DOI: 10.1007/s40195-016-0518-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Copper Nanospheres and Nanocubes and Their Antibacterial Activity Against Escherichia coli and Enterococcus sp.

Abstract: Abstract:The interest in synthesising inorganic nanomaterials for biological applications has increased in recent years, especially for antibacterial purposes. In the present study, spherical and cube-shaped copper nanoparticles were synthesised by a chemical reduction method and their efficacy as antimicrobial agents against both Gram-negative (Escherichia coli) and Gram-positive (Enterococcus sp) organisms investigated. The nanoparticles were characterised using ultra-violet/visible spectroscopy, scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…In addition to size, the shape of the nanoparticles can also influence their intrinsic properties, for example, photocatalytic properties can be affected, largely through enhanced surface area while plasmonic properties are influenced by the nanomaterials shape which affects the relative lengths along which the electron cloud can resonate and hence the specific wave function. [ 73 ] With improvements in nanotechnology and fabrication processes, a diverse array of nanoscale shapes have been constructed, such as: nanoparticles, [ 74 ] nanodots, [ 75 ] nanocubes, [ 76,77 ] nanorods, [ 78,79 ] nanoshells, [ 80 ] nanocages, [ 81 ] nanostars, [ 82 ] nanoflowers, [ 83 ] nanoeggs, [ 84 ] nanopopcorn, [ 85 ] and numerous other 2D materials. [ 86,87 ] Figure shows a variety of commonly investigated nanomaterials, along with experimentally obtained images of example nanomaterials with the corresponding shape.…”
Section: Fundamental Aspects Of Metal Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to size, the shape of the nanoparticles can also influence their intrinsic properties, for example, photocatalytic properties can be affected, largely through enhanced surface area while plasmonic properties are influenced by the nanomaterials shape which affects the relative lengths along which the electron cloud can resonate and hence the specific wave function. [ 73 ] With improvements in nanotechnology and fabrication processes, a diverse array of nanoscale shapes have been constructed, such as: nanoparticles, [ 74 ] nanodots, [ 75 ] nanocubes, [ 76,77 ] nanorods, [ 78,79 ] nanoshells, [ 80 ] nanocages, [ 81 ] nanostars, [ 82 ] nanoflowers, [ 83 ] nanoeggs, [ 84 ] nanopopcorn, [ 85 ] and numerous other 2D materials. [ 86,87 ] Figure shows a variety of commonly investigated nanomaterials, along with experimentally obtained images of example nanomaterials with the corresponding shape.…”
Section: Fundamental Aspects Of Metal Nanomaterialsmentioning
confidence: 99%
“…This renewed interest coincides with significant breakthroughs in the understanding, fabrication and characterization of sub‐micron‐sized materials. A wide range of nanomaterials have been demonstrated to possess antimicrobial effects, including iron (III) oxide, [ 106 ] zinc oxide, [ 107 ] magnesium oxide, [ 108 ] silver, [ 67,109 ] gold, [ 110 ] copper [ 45,77 ] and copper oxide, [ 111 ] calcium oxide, [ 41 ] titanium dioxide [ 112 ] and cadmium oxide [ 113 ] among others. [ 41,42,87,114,115 ] Successful antimicrobial activity has been demonstrated utilizing an equally wide array of shapes (Figure 2).…”
Section: Passive Antimicrobial Mechanisms Of Metal Nanomaterialsmentioning
confidence: 99%
“…The physical shape of the nano-metal is an important factor, affecting its ability to interact with the bacterial membrane, as well as the generation of ROS. A variety of shapes can be formed, including nanocubes [35][36][37], nanospheres [37,38], flat nanosheets [39], nanorods [40][41][42], nanoclusters [43][44][45] and nanoprisms [46] which all produce different levels of antibacterial effect. Alshareef et al, tested the antibacterial efficacy of copper nanospheres and nanocubes against the gram-negative strain Escherichia coli and the gram-positive strain Enterococcus sp.…”
Section: Factors Affecting the Antibacterial Activity Of Nano-metal And Nano-metal Oxidesmentioning
confidence: 99%
“…Alshareef et al, tested the antibacterial efficacy of copper nanospheres and nanocubes against the gram-negative strain Escherichia coli and the gram-positive strain Enterococcus sp. Tests demonstrated that both copper nanospheres and nanocubes were effective against both gram positive and negative strains, however the nanocube morphology had the greatest antimicrobial effect, which suggests that the cubic profile resulted in higher levels of reactivity against the bacterial strains [37]. Zhang et al created a composite nanosheet comprising of polydopamine-graphene nanosheet-nanosilver, for antibacterial testing against gram-negative Escherichia coli and gram-positive B. subtilis.…”
Section: Factors Affecting the Antibacterial Activity Of Nano-metal And Nano-metal Oxidesmentioning
confidence: 99%
“…Some examples of organic antimicrobial agents include quaternary ammonium salts, halogenated compounds, organic acids, and phenols; natural materials are based on materials such as chitosan and chitin [ 22 ]. Inorganic antimicrobial agents, including metals and metal ions, metal oxide nanoparticles including TiO 2 [ 43 ], ZnO [ 44 ], silver [ 45 ], gold [ 46 ], magnesium oxide [ 47 , 48 ] copper [ 49 ], copper oxide [ 50 ], iron (III) oxide [ 51 ], and CaO [ 52 ], have attracted considerable interest in food packaging researches due to their stability, especially under the different conditions imposed in food packaging [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%